Religiosity of the prospective members of the Stańczycy group in their youth in comparison with their later religious views - Mateusz Piotr Gancewski (Folia Historica Cracoviensia)
This article discusses the religious views of Stanisław Koźmian, Ludwik Wodzicki and Stanisław Tarnowski, as well as the shape of their piety before the January Uprising. The religiousness of their youth was confronted and compared with their later religious views, which allowed for a change in their views over the years.